2007
DOI: 10.1128/iai.00735-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Mutants Lacking the Golgi UDP-Galactose or GDP-Mannose Transporters Establish that Phosphoglycans Are Important for Promastigote but Not Amastigote Virulence in Leishmania major

Abstract: Abundant surface Leishmania phosphoglycans (PGs) containing [Gal(␤1,4)Man(␣1-PO 4 )]-derived repeating units are important at several points in the infectious cycle of this protozoan parasite. PG synthesis requires transport of activated nucleotide-sugar precursors from the cytoplasm to the Golgi apparatus. Correspondingly, null mutants of the L. major GDP-mannose transporter LPG2 lack PGs and are severely compromised in macrophage survival and induction of acute pathology in susceptible mice, yet they are abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 67 publications
6
63
0
Order By: Relevance
“…4, A and B). In previous studies of other mutant L. major, we showed that the delayed lesion phenotype similar to that seen with gcvP Ϫ metacyclic promastigotes infections arose from stage-specific effects (27,(45)(46)(47). In such mutants, the ability of the metacyclic promastigote to establish infections in macrophages and/or mice was compromised but not its ability to replicate and induce pathology as the amastigote stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4, A and B). In previous studies of other mutant L. major, we showed that the delayed lesion phenotype similar to that seen with gcvP Ϫ metacyclic promastigotes infections arose from stage-specific effects (27,(45)(46)(47). In such mutants, the ability of the metacyclic promastigote to establish infections in macrophages and/or mice was compromised but not its ability to replicate and induce pathology as the amastigote stage.…”
Section: Discussionmentioning
confidence: 99%
“…WT and gcvP Ϫ /ϩGCVP parasites persisted at similar levels (3,300 Ϯ 7,100 WT parasites per lesion, n ϭ 5; 2,200 Ϯ 2,700 gcvP Ϫ /ϩGCVP parasites per lesion, n ϭ 8), whereas gcvP Ϫ were found at somewhat higher levels (9,300 Ϯ 14,000 parasites per lesion, n ϭ 9), although this difference was not statistically significant. gcvP Ϫ Amastigotes Show Attenuated Virulence-In previous studies of other mutant L. major, we showed that a "delayed lesion" phenotype similar to that seen with gcvP Ϫ metacyclic promastigote infections arose from a defect in the virulence of metacyclic promastigotes but not of amastigotes (27,(45)(46)(47). This model was tested here by purifying amastigotes from gcvP Ϫ -infected mice showing significant pathology and inoculating them directly back into mice as amastigotes (Fig.…”
Section: Gcvp Gene Comparison and Gcvp Localization-datamentioning
confidence: 99%
“…However, our recent studies of another PG-deficient L. major mutant, obtained through inactivation of the UDP-Gal transporters encoded by the LPG5A and LPG5B genes (lpg5A Ϫ lpg5B Ϫ ), question this assumption. Unexpectedly, the lpg5A Ϫ lpg5B Ϫ mutant resembled the lpg1 Ϫ rather than the lpg2 Ϫ parasites, by displaying a virulence defect when tested as promastigotes but showing normal virulence as amastigotes (7,8). This suggests that a loss of LPG2-dependent glycoconjugates, other than PGs, may underlie the virulence defect of lpg2 Ϫ L. major.…”
mentioning
confidence: 90%
“…Ϫ , lpg2 AB, and lpg5A Ϫ lpg5B Ϫ mutants were derivatives of the WT L. major strain LV39 clone 5 (Rho/SU/59/P) and were made by homologous gene targeting as described previously (7,8,43,45). Parasites were cultured at 26°C in M199 medium (HyClone, Logan, UT) supplemented with 10% heat-inactivated fetal bovine serum (FBS) (Cansera, Mississauga, Ontario, Canada), 2 mM L-glutamine, 100 U/ml penicillin, and 100 g/ml streptomycin (Invitrogen Life Technologies, Burlington, Ontario, Canada).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation